Absolute Positioning Using the Earth's Magnetic Anomaly Field. Issue 2 (21st June 2016) - Canciani, Aaron; Raquet, John
Abstract: Achieving worldwide dependable alternatives to the Global Positioning System is a challenging engineering problem. Current Global Positioning System alternatives often suffer from limitations such as where and when the systems can operate. Navigation using Earth's magnetic anomaly field, which is globally available at all times, shows promise to overcome many of these limitations. We present a navigation framework that uses Earth's magnetic anomaly field as a navigation signal to aid an inertial navigation system in an aircraft. The filter utilizes ultra‐accurate optically pumped cesium magnetometers to make scalar intensity measurements of Earth's magnetic field and compare them with a map using a particle filter approach. The accuracy of these measurements allows observability of not only the inertial navigation system errors but also the temporal effects of Earth's magnetic field, which corrupt the navigation signal. These temporal effects are thoroughly analyzed, and we present a simple model that allows near worldwide use of the navigation filter. We analyze the dependencies on altitude and magnetic storm activity in a realistic simulation using data from test flights and magnetic observatories. Copyright © 2016 Institute of Navigation